Microstructural changes of whole brain in patients with comitant strabismus: evidence from a diffusion tensor imaging study - Huang X; Li H; Zhang Y; Peng D; Hu P; Zhong Y; Zhou F; Shao Y (Neuropsychiatric Disease and Treatment)
Xin Huang,1,2,* Hai-Jun Li,3,* Ying Zhang,1 De-Chang Peng,3 Pei-Hong Hu,1 Yu-Lin Zhong,1 Fu-Qing Zhou,3 Yi Shao1 1Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Nanchang, 2Department of Ophthalmology, The First People’s Hospital of Jiujiang City, Jiujiang, 3Department of Radiology, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China*These authors contributed equally to this work Objective: The aim of this study was to investigate the fractional anisotropy (FA) and mean diffusivity (MD) using a diffusion tensor imaging technique and whole-brain voxel-based analysis in patients with comitant strabismus.Patients and methods: A total of 19 (nine males and ten females) patients with comitant strabismus and 19 age-, sex-, and education-matched healthy controls (HCs) underwent magnetic resonance imaging examination. Imaging data were analyzed using two-sample t-tests to identify group differences in FA and MD values. Patients with comitant strabismus were distinguishable from HCs by receiver operating characteristic curves.Results: Compared with HCs, patients with comitant strabismus exhibited significantly decreased FA values in the brain regions of the left superior temporal gyrus and increased values in the bilateral medial frontal gyrus, right globus pallidus/brainstem, and bilateral precuneus. Meanwhile, MD value was significantly reduced in the brain regions of the bilateral cerebellum posterior lobe and left middle frontal gyrus but increased in the brain regions of the right middle frontal gyrus and left anterior cingulate.Conclusion: These results suggest significant brain abnormalities in comitant strabismus, which may underlie the pathologic mechanisms of fusion defects and ocular motility disorders in patients with comitant strabismus. Keywords: comitant strabismus, diffusion tensor imaging, mean diffusivity, fractional anisotropy, resting state